Synthesis, Characterization and Study of Electrical Properties of Some New Aromatic Polyester - Basma. J. Ahmed (Journal of Global Pharma Technology, 2018)
This research discloses the synthesis of various polyester resins, the polyesters containing homoring aromatic and others heterocyclic were synthesized by the condensation polymerization of suitable monomers (which are containing variety function groups in different structures) with phthalic anhydride. The main objective is synthesis of new polyester with keeping a reasonable electrical insulating behavior. The structural of polymer was characterized by Fourier Transform infra-red spectroscopy FTIR and HNMR. The dielectric constant (real ε' and imaginary parts ε") and AC conductivity (σAC) for all the polyester samples are studied by varying the frequency (30, 50, 70, 90, 120, 300, 500Hz and 1KHZ) at 25⁰C. Indeed, study of the electrical behavior of various polyesters revealed that the cross-linked polyesters presents higher insulating behavior at room temperature than linear polymers. Thermo gravimetric analysis (TGA) and differential scanning calorimetry (DSC) were employed to study the thermal stability for these polymers.Keywords: Aromatic polyester, Condensation polymerization, Heterocyclic, Phthalic anhydride, Thermal stability.